3D Printed Polymer Photodetectors. Issue 40 (28th August 2018) - Park, Sung Hyun; Su, Ruitao; Jeong, Jaewoo; Guo, Shuang‐Zhuang; Qiu, Kaiyan; Joung, Daeha; Meng, Fanben; McAlpine, Michael C.
Abstract: Extrusion‐based 3D printing, an emerging technology, has been previously used in the comprehensive fabrication of light‐emitting diodes using various functional inks, without cleanrooms or conventional microfabrication techniques. Here, polymer‐based photodetectors exhibiting high performance are fully 3D printed and thoroughly characterized. A semiconducting polymer ink is printed and optimized for the active layer of the photodetector, achieving an external quantum efficiency of 25.3%, which is comparable to that of microfabricated counterparts and yet created solely via a one‐pot custom built 3D‐printing tool housed under ambient conditions. The devices are integrated into image sensing arrays with high sensitivity and wide field of view, by 3D printing interconnected photodetectors directly on flexible substrates and hemispherical surfaces. This approach is further extended to create integrated multifunctional devices consisting of optically coupled photodetectors and light‐emitting diodes, demonstrating for the first time the multifunctional integration of multiple semiconducting device types which are fully 3D printed on a single platform. The 3D‐printed optoelectronic devices are made without conventional microfabrication facilities, allowing for flexibility in the design and manufacturing of next‐generation wearable and 3D‐structured optoelectronics, and validating the potential of 3D printing to achieve high‐performance integrated active electronic materials and devices. Abstract : Fully 3D‐printed polymer photodetectors are demonstrated on flexible substrates and hemispherical surfaces to integrate multidimensional image sensing arrays with high sensitivity and wide field of view. 3D printing multifunctional optoelectronic devices on a single platform is possible from a one‐pot, custom‐built extrusion‐based 3D manufacturing system. This work opens the possibility of the "off‐grid" printing of next‐generation wearable optoelectronic devices.